Gynura procumbens leaf improves blood glucose level, restores fertility and libido of diabetic-induced male rats - Khaidatul Akmar Kamaruzaman,; Mahanem Mat Noor, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Gynura procumbens (GP) has been widely used in traditional medicine due to its ability in treating various types of diseases. This study was carried out to determine the effects of GP on blood glucose level, fertility and libido of streptozotocin-induced male rats. A total of 42 male rats were randomly sorted into six groups; normal, negative and positive controls and three treated groups with different dosages of GP aqueous extract (GPAE); 150, 300 and 450 mg/kg. Each group was treated via oral feeding for 14 consecutive days. The rats were sacrificed on day 15 for further analysis. Administration of GPAE significantly lowered the fasting blood glucose (FBG) level and increased the plasma testosterone level of diabetic-induced rats compared to the positive and negative control groups. There was also a significant increase in the sperm quality as well as the fertility of GPAE treated groups compared to the negative and positive control groups. Sexual behaviour analysis demonstrated that GPAE is able to facilitate the expression of sexual behaviour significantly; increased mounting frequency and reduced mounting latency. These lines of evidence suggested that GPAE can act as antihyperglycaemic, profertility and libido agents. However, its mechanism(s) remains unresolved.